A Study on the Antecedents and Consequences of Diversity Beliefs in Organization - Ju, YeongKyeong; Kim, MyoungSo (Korean Journal of Industrial and Organizational Psychology, 2020)
The purpose of this study was to (1) explore the predictors of individual and situational characteristics that affect the diversity beliefs of employees within an organization, and (2) examine the impact of diversity beliefs on their job performance as well as emotional commitment. A total of 300 employees working at various fields in Korea participated in on-line survey. The results of the hierarchical multiple regression analyses showed that the individual characteristics like agreeableness, extroversion, openness of HEXACO personality factors, need for uniqueness, perspective taking, and growth mindset were the significant predictors of diversity beliefs. It was also found that the situational characteristics such as diversity climate and inclusive leadership had significant effects on diversity beliefs. Furthermore, the impacts of pro-diversity beliefs on task performance, contextual performance, adaptive performance, and emotional commitment were all significant, supporting the predictive power of the diversity beliefs on individual job effectiveness. The results of structural equation models demonstrated the core predictors of the diversity beliefs were need for uniqueness, perspective taking, growth mindset, and diversity climate. We proposed a model that includes these predictors and 4 criteria of diversity beliefs, and the fitness of the models on each of job effectiveness were all acceptable. Finally, the implications and future research directions were discussed based on the findings.